2019
DOI: 10.18203/2320-6012.ijrms20191547
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of respiratory morbidity among brick kiln workers: a cross sectional study from rural north India

Abstract: Background: Fired clay bricks, an important construction material, are manufactured in non-mechanized, labour intensive brick kilns which mostly employ unskilled men and women. The workers, as an occupational hazard, are exposed to dust and air pollution leading to respiratory diseases.Methods: This cross sectional study was conducted among brick kiln workers in RS Pura block of Jammu district. The workers were assessed regarding respiratory symptoms and illnesses using translated version of American Thoracic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Furthermore, it is supported by the findings of Permatasari's 2018 study, which found that total dust particle levels were a risk factor for the incidence of symptoms of respiratory disorder. Field interviews revealed that, while overall dust particle levels surpassed the threshold value, the dose of exposure that entered the worker's body varied depending on the time of exposure and the usage of personal protective equipment (Gupta et al, 2019a). The findings of this study are also consistent with Mirza's research from 2021, which found an association between total dust exposure and respiratory illnesses (p value = 0.048) (Fuadi et al, 2021).…”
Section: Relationship Between Total Dust Particulate Level With Sympt...supporting
confidence: 86%
See 2 more Smart Citations
“…Furthermore, it is supported by the findings of Permatasari's 2018 study, which found that total dust particle levels were a risk factor for the incidence of symptoms of respiratory disorder. Field interviews revealed that, while overall dust particle levels surpassed the threshold value, the dose of exposure that entered the worker's body varied depending on the time of exposure and the usage of personal protective equipment (Gupta et al, 2019a). The findings of this study are also consistent with Mirza's research from 2021, which found an association between total dust exposure and respiratory illnesses (p value = 0.048) (Fuadi et al, 2021).…”
Section: Relationship Between Total Dust Particulate Level With Sympt...supporting
confidence: 86%
“…The inability of personnel to use PPE, such as masks, while performing their jobs can result in symptoms of respiratory disorder (Gupta et al, 2019b). Alternative solutions to issues were revealed by research done by Ipmawati in 2018 including recommendations for personal protective equipment that can be pursued as an early protection measure against accidents and occupational diseases that arise in the workplace environment, then implementing fundamental policies regarding the application of occupational safety and health at work to minimize the number of occupational diseases, especially dust (Ipmawati PA, 2018).…”
Section: Relationship Between the Uses Of Personal Protective Equipme...mentioning
confidence: 99%
See 1 more Smart Citation